Preoperative computed tomography-guided localization pulmonary nodules: comparison between accura and soft anchored wires - Zhou, Feng; Tao, Jun; Shen, Fei; Huang, Xiang-Zhong; Huang, Wen-Jia; Gao, Fu-Lei (Frontiers in Surgery, 2025)
BackgroundBoth Accura wire and soft anchored wire strategies can be employed for the preoperative computed tomography (CT)-guided localization of pulmonary nodules (PNs). The relative outcomes associated with these two distinct localization strategies, however, remain uncertain. This study thus sought to explore the relative safety and efficacy of preoperative CT-guided Accura wire and soft anchored wire localization for PNs.MethodsThis was a retrospective study enrolling patients from two centers. Consecutive patients with PNs who underwent preoperative CT-guided Accura wire or soft anchored wire localization followed by video-assisted thoracic surgery (VATS) resection between January 2022 and December 2023 were enrolled in these analyses. The comparison was carried out between these two groups to evaluate the safety and efficacy.ResultsOver the course of this study, 190 patients were enrolled and classified into the Accura wire (n = 100) and soft anchored wire (n = 90) groups. One PN was localized per patient, and the respective technical success rates for these two localization strategies were 98% (98/100) and 100% (P = 0.497). Dislodgement accounted for the two technical failures in the Accura wire group. Comparison of both groups revealed a comparable median localization procedural duration (9.0 vs. 9.0 min, P = 0.082), while the soft anchored wire group presented with visual analog scale scores significantly lower than those for the Accura wire group (3.0 ± 0.6 vs. 4.5 ± 0.6, P = 0.001). Significantly reduced pneumothorax (16.7% vs. 41%, P = 0.001) and pulmonary hemorrhage (23.3% vs. 41%, P = 0.01) rates were noted for the soft anchored wire relative to the Accura wire. VATS-guided limited resection was successfully performed for all patients.ConclusionsBoth Accura wire and soft anchored wire strategies can facilitate accurate PN localization prior to VATS, although the latter strategy may be associated with a better safety profile relative to the former.